2012
DOI: 10.1186/1471-2261-12-62
|View full text |Cite
|
Sign up to set email alerts
|

Utility of nuclear stress imaging for detecting coronary artery bypass graft disease

Abstract: BackgroundThe value of Single Photon Emission Computed Tomography stress myocardial perfusion imaging (SPECT-MPI) for detecting graft disease after coronary artery bypass surgery (CABG) has not been studied prospectively in an unselected cohort.MethodsRadial Artery Versus Saphenous Vein Graft Study is a Veterans Affairs Cooperative Study to determine graft patency rates after CABG surgery. Seventy-nine participants agreed to SPECT-MPI within 24 hours of their coronary angiogram, one-year after CABG. The choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…While the magnitude of decrease in LVEF was small (mean 3% reduction), which may not have any clinical significance, the change in EF ranged from −33% to 15%, meaning that some patients had a clinically significant decline in EF. A decrease in LV systolic function with CABG surgery may result from intra-operative global ischemia (15) or myocardial stunning (16), or from early post-operative graft failure (17). These results warrant confirmation in prospective studies with unselected patients.…”
Section: Discussionmentioning
confidence: 96%
“…While the magnitude of decrease in LVEF was small (mean 3% reduction), which may not have any clinical significance, the change in EF ranged from −33% to 15%, meaning that some patients had a clinically significant decline in EF. A decrease in LV systolic function with CABG surgery may result from intra-operative global ischemia (15) or myocardial stunning (16), or from early post-operative graft failure (17). These results warrant confirmation in prospective studies with unselected patients.…”
Section: Discussionmentioning
confidence: 96%
“…The use of FFR testing in bypass grafts, for instance, has not been subject to extensive prospective validation. Regarding the use of non‐invasive imaging in such patients, published studies in this area have been very small but have suggested comparable accuracy (74–82%) for the detection of graft stenoses . While a positive non‐invasive stress test was an independent predictor of subsequent revascularization, such testing overall had very limited specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers claimed that the results of the myocardial perfusion imaging were not concordant with angiographic findings, which was possibly due to the nature of this disease (nonfixed lesion). In another study, the investigator examined the value of using SPECT-MPI to detect the graft disease after a coronary artery bypass surgery (CABG), and it was claimed that “SPECT-MPI has a good sensitivity and accuracy for detecting graft disease in an unselected patient population 1 year post-CABG under optimal stress conditions” (with the presence of variation in accuracy and sensitivity of SPECT-MPI between the exercise stress test and the pharmacological stress test) [ 14 ]. On the other hand, Shelley and his colleagues [ 15 ] have attempted to compare SPECT-MPI with multislice computed tomography (MSCT), and it was found that “whenever MSCT was negative, MPI was almost negative.” In addition, a study conducted by Delcour et al [ 16 ] included 48 patients with normal CAG and abnormal MPI who were followed up for at least 3 years from the conduction of MPI.…”
Section: Discussionmentioning
confidence: 99%